ANALISIS PERBANDINGAN CAMEL PADA BANK BCA SYARIAH SEBELUM DAN SELAMA PANDEMI COVID-19 - Intan Purnama Sari; Erric Wijaya (Journal of Accounting, Management and Islamic Economics, 2024)
The Covid-19 pandemic has had an impact on various aspects of the economy and business activities. The Covid-19 pandemic has an impact on banking and financial performance which will af ect the level of bank health. There is a way that can be done to determine the impact of the pandemic regarding bank health, namely by requiring objective and precise benchmarks. This research aims to analyze financial reports on the performance of Sharia Banks before the Covid-19 pandemic and during the Covid-19 pandemic. The data analysis method applied in this research is quantitative descriptive analysis. Quantitative analysis is a scientific method because it meets scientific principles, namely empirical concreteness, objective, measurable, rational and systematic. This analysis uses research data in the form of numbers and carries out statistical analysis (Sugiyono, 2013). Then, the analysis tool in this research uses the time series data analysis model. The sampling method in this research is Non-Probability Sampling. The sampling technique for this research is saturated sampling. 12 samples were applied before the Covid-19 pandemic and 12 samples were applied during the Covid-19 pandemic. The testing tool used is SPSS version 24. The research results show that the CAMEL method shows that in the Capital Adequacy Ratio, Non Performing Financing, BOPO ratios there is a significant dif erence between before the Covid-19 pandemic and during the Covid-19 pandemic, while the Return on Assets indicator shows that there is no significant dif erence between before and during the Covid-19 pandemic. Financing to Deposit Ratio shows that there is no significant dif erence between before and during the Covid-19 pandemic.